Tuberculosis outbreak in a nursing home involving undocumented migrants and Israeli citizens - Mor, Z. (Isr J Health Policy Res, 2018)
OBJECTIVES: Israel has absorbed > 60,000 migrant from the horn of Africa (MHOA) since 2006. No cross-transmission of Mycobacterium tuberculosis from MOHA to Israeli citizens has yet been reported. This study describes the results of contact investigation and laboratory work-out of a unique mixed cluster which included both MOHA and Israeli citizens. METHODS: Description of the results of epidemiological investigation including laboratory confirmation. RESULTS: This unique Mycobacterium tuberculosis strain included 29 patients: 26 were MOHA and three citizens who immigrated to Israel from the former Soviet Union. This is the first mixed cluster described in Israel, which has not been represented in the SITVIT international database of genotyping markers. The transmission from non-citizens to citizens occurred in a nursing institution, when MOHA infected three other contacts- two of whom were retarded residents, one of them died. The index case was screened before employment, and was permitted to return to wok although his chest X-ray demonstrated radiological findings compatible with tuberculosis. Epidemiological links were found in other 12 MOHA members of the cluster. CONCLUSION: This report describes cross-transmission of Mycobacterium tuberculosis from non-citizens MOHA to Israeli citizens who were residents of a nursing home, which may be the first sign for an epidemiological shift. Although cross-ethnical transmission is still rare in Israel, medical settings should employ efficient infection control measures to protect both patients and staff from Mycobacterium tuberculosis.